Hypocalcemia is associated with severe COVID-19: A systematic review and meta-analysis. Issue 1 (January 2021) - Martha, Januar Wibawa; Wibowo, Arief; Pranata, Raymond
Abstract: Background and aims: Hypocalcemia is commonly in critically ill patients and studies have shown that hypocalcemia is prevalent in patients with COVID-19. This meta-analysis aimed to evaluate the prognostic performance of hypocalcemia in patients with coronavirus disease 2019 (COVID-19). Methods: We performed a systematic literature search on PubMed, Scopus, and Embase with keywords "SARS-CoV-2″ OR″COVID-19″ OR ″2019-nCoV" AND "hypocalcemia" up until 10 December 2020. The key exposure was hypocalcemia, defined as serum calcium below study-defined cut-off points. The main outcome was poor outcome, which was a composite of mortality and severity. The effect estimate of the main outcome was reported as odds ratio (OR) and its 95% confidence interval (95% CI). We also generate sensitivity, specificity, positive and negative likelihood ratio (PLR & NLR), diagnostic odds ratio (DOR), and area under curve (AUC). Results: There are 2032 patients from 7 studies included in this systematic review and meta-analysis. The incidence of poor outcome in this study was 26%. Serum calcium was lower in patients with poor outcome (mean difference −0.173 mmol/L [-0.259,  −0.087], p < 0.001; I 2 : 31.3%). Hypocalcemia was associated with poor outcome (OR 3.19 [2.02, 5.06], p < 0.001; I 2 : 32.86%); with sensitivity of 0.74 [0.53, 0.88], specificity of 0.54 [0.29, 0.77], PLR of 1.6 [1.1, 2.3], NLR of 0.49 [0.35, 0.66], DOR of 3 [2, 5], and AUC of 0.70 [0.66, 0.74]. In this pooled analysis, the post-test probability was 36% in patients with hypocalcemia and 15% in patients without hypocalcemia. Conclusion: Hypocalcemia was associated with poor outcome in COVID-19 patients. PROSPERO ID: CRD42020225506. Highlights: Hypocalcemia was associated threefold increase in poor outcome. Hypocalcemia has a 74% sensitivity, 54% specificity, and AUC of 0.70 for predicting poor outcome. In this analysis, post-test probability of poor outcome in patients with and without hypocalcemia was 36% and 15% respectively.